The impact of teachers’ perceived competence in information and communication technology usage, and workplace anxiety on well-being, as mediated by emotional exhaustion - Chen, Bo-Ching; Wu, Yu-Tai; Chuang, Ya-Ting (Frontiers in Psychology, 2024)
The 2030 Sustainable Development Goals (SDGs) were adopted by the United Nations in 2015. They emphasize the importance of achieving peace, prosperity and well-being for all people. Sustainable health has become an important issue, with the outbreak of the COVID-19 pandemic, teachers were forced to adopt distance teaching, which made it necessary for them to quickly upgrade their ICT skills and integrate them into e-learning, which caused tangible and intangible pressures on teachers and had an impact on their well-being. A quantitative research methodology and a questionnaire survey was used as the primary research design. This study examined the effects of ICT competence on teachers' workplace anxiety, emotional exhaustion, and well-being during the pandemic from the perspective of Social Cognitive Theory (SCT) with a total of 21 questions. In this study, the snowball method was used as a sampling method for online questionnaires from September to October 2021. A total of 216 questionnaires were collected, of which four incomplete questionnaires were excluded, leaving a total of 212 valid questionnaires, with a valid questionnaire recovery rate of 98.1%. The valid questionnaires were analyzed using Smart Pls 4.0 Partial Least Square Method Structural Equation Modeling (PLS-SEM). Lastly, teachers' ICT competence could significantly reduce emotional exhaustion and enhance teachers' well-being.However, there was no significant effect on workplace anxiety. Additionally, well-being was not directly affected by workplace anxiety, and teachers' well-being needs to be mediated by emotional exhaustion to be indirectly affected. This study found that teachers' ICT competence could significantly reduce emotional exhaustion and enhance teachers' well-being, but the effect on workplace anxiety was not significant. Finally, this study reveals that emotional exhaustion plays an important mediating role between teachers' ICT competence and workplace stress, both of which are important mediators of well-being. From a practical point of view, to achieve the Sustainable Development Goals (SDGs) 2030 it is ideal to have good health and well-being for the whole person.This study facilitates the development of strategies to improve the well-being of teachers, which provides an empirical basis for the enhancement of mental health and well-being of educators.